Urinary incontinence nursing diagnoses in patients with stroke - Telma Alteniza Leandro; Thelma Leite de Araujo; Tahissa Frota Cavalcante; Marcos Venícios de Oliveira Lopes; Tyane Mayara Ferreira de Oliveira; Ana Cecília Menezes Lopes (SciELO, 2015)
Abstract OBJECTIVE Identifying the prevalence of Stress urinary incontinence (SUI), Urge urinary incontinence (UUI), Functional urinary incontinence (FUI), Overflow urinary incontinence (OUI) and Reflex urinary incontinence (RUI) nursing diagnoses and their defining characteristics in stroke patients. METHOD A cross-sectional study with 156 patients treated in a neurological clinic. Data were collected through interviews and forwarded to nurses for diagnostic inference. RESULTS 92.3% of the patients had at least one of the studied diagnoses; OUI showed the highest prevalence (72.4%), followed by FUI (53.2%), RUI (50.0%), UUI (41.0%) and SUI (37.8%). Overdistended bladder and reports of inability to reach the toilet in time to avoid urine loss were the most prevalent defining characteristics. A statistically significant association of the defining characteristics with the studied diagnosis was verified. CONCLUSION The five incontinence diagnoses were identified in the evaluated patients, with different prevalence.